BAGURAU SALUANG DENDANG IN THE PERFORMANCE LAPIAK GURAU IN THE MINANGKABAU COMMUNITY IN TANAH DATAR DISTRICT: CONTINUITY CHANGE AND FUNCTION - Amelia, Putri Chairina; Nasution, Ikhwanuddin; Sebayang, Vanesia Amelia (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
The Bagurau Saluang Dendang performance referred to in this research is the Bagurau Saluang Dendang performance at the Lapiak Gurau event, literally meaning 'joking on a mat', which usually occurs in many coffee shops in Tanah Datar Regency. This show is an entertainment show. This thesis aims to analyse the changes that occur in the Lapiak Gurau Saluang Dendang (TLGSD) tradition performance today. This performance is usually performed at night, from 20.00 WIB until dawn. The accompanying instrument for singing in this performance is usually only the saluang musical instrument. Meanwhile, the singers are only men. This is because traditional rules prohibit the participation of women in bagurau art. In the early 2000s, changes began to occur. In fact, nowadays, TLGSD performances are held from 22.00 WIB until just before dawn. The cast in TLGSD currently numbers ten people, with details: one saluang player, one keyboard player, one Janang, four singing children, and three singing parents. Changes in the mindset of the Minangkabau people in the last three or four decades have had an impact on the orientation of TLGSD performances. The changes in question predominantly occurred in aspects of the procedures for performing lapiak gurau, including traditional norms for female singers, the choice of ensemble format used as accompaniment to the song, and the text of the pantun. The method used in this research is a qualitative-descriptive method using an ethnographic perspective. The results of this research show that the tradition of lapiak gurau saluang dendang has undergone changes: (i) the choice of instruments to accompany the dang that is popular with audiences is now more modern; (ii) the majority of singers currently in demand as singers are women; (iii) weakening the role of the ninik mamak as traditional elders who are supposed to protect the dignity of Minangkabau women. However, TLGSD is now contributing to increasing the financial income of stall owners.